Effects of chemically synthesized kava-kava (Piper methysticum g.forst) flavokawain A and B on the apoptotic and metastatic process of MCF -7 and MDA - MB231 cells in vitro and 4T1 cells in vivo - Abu, Nadiah (2014)
In Malaysia, breast cancer is becoming a more prominent health issue among women today. Unfortunately, most malignant breast cancer will tend to metastasize to distant locations and form secondary tumors. This is usually the main cause of cancer-related deaths. Therefore, it is imperative to not actually treat cancer but to halt the metastatic process altogether. Though a number of approaches can be used to treat this disease, the prognosis tends to be unfavorable due to unwanted side effects and development of resistance. Natural products still remain one of the most sought after sources to find the perfect cure for cancer. The kava-kava (Piper methysticum) plant has been well known to aid illnesses and harness remedies since ancient times, especially in the pacific region. There are two classes of molecules that can be extracted from this kava-kava plant, kavalactones and chalcones. Chalcones can be divided into three types, flavokawain A, flavokawain B and flavokawain C. This project aims to study the effects of flavokawain A and B in the apoptotic and metastatic process in, MCF7 and MDA-MB231. Notably, both flavokawain A and B were non-toxic in both in vitro and in vivo experiments using Balb/C mice after 28 days of treatment. Through the MTT assay, it was found that both flavokawain A and B were cytotoxic in both breast cancer cell lines. Both flavokawain A and flavokawain B managed to induce apoptosis significantly as evidenced by these assays; double staining acridine orange/propidium iodide, flow cytometry cell cycle analysis, Annexin V analysis, JC-1, Caspase 8/9 fluorometric assay and BrdU cell proliferation assay. The results suggest that both flavokawain A and B induce G2/M arrest and apoptosis in both cell lines. Additionally, metastasisrelated assays were also conducted such as; wound healing assay, migration and invasion assay, HUVEC tube formation and rat aortic ring assay. Flavokawain A and flavokawain B were shown to possess promising anti-metastatic potential. To further elucidate the apoptotic and anti-metastatic mechanism of flavokawain A and B at the molecular level, real time polymerase chain reaction and western blot were conducted. Even though both molecules pose similar mechanism of action, flavokawain B is more potent and active than flavokawain A in terms of the induction of cell death and inhibition of metastasis. This notion was put to test in an in vivo setting whereby the compounds were used to treat 4T1 cells (mouse breast cancer) in mice. Based on the results, both flavokawain A and flavokawain B reduced the size of the tumor in vivo. In conclusion, flavokawain B is seemingly a better candidate as an anti-cancer agent than flavokawain A as evidenced by the in vitro assays. Moreover, based on the metastatic potential, flavokawain B was also a much more potent agent than flavokawain A. This concept was also proven by the in vivo assays using 4T1-breast cancer cell challenged mice. This study was able to elucidate the mechanism of action of both flavokawain A and flavokawain B in terms of its anti-cancer properties.